Bifurcation PCI with a hybrid strategy with drug- eluting balloons versus a stepwise provisional two- stent strategy: Rationale and design of the hybrid DEB study - Dillen, Daimy M.M.; Vlaar, Pieter Jan; Vermeer, Amy J.E.; Paradies, Valeria; van Kuijk, Jan- Peter; Vink, Maarten A.; Oemrawsingh, Rohit M.; Hofma, Sjoerd H.; Magro, Michael; Remkes, Wouter S.; de Smet, Bart J.G.L.; van Rees, Johannes B.; et al. (The American heart journal, 2023)
The optimal treatment strategy for coronary bifurcation lesions by percutaneous coronary intervention (PCI) is complex and remains a subject of debate. Current guidelines advise a stepwise provisional approach with optional two-stent strategy. However, a two-stent strategy, both upfront and stepwise provisional, is technically demanding. Therefore, there is increasing interest in the use of drug-eluting balloons (DEB) in bifurcation lesions, mainly after a provisional approach with unsatisfactory result of the side branch. Some small pilot studies already showed that the use of DEB in bifurcation lesions is safe and feasible. However, a randomized comparison of this hybrid DEB strategy with a two-stent strategy is currently lacking. The Hybrid DEB study is a prospective, multicenter, randomized controlled trial investigating noninferiority of a hybrid DEB approach, using a combination of a drug-eluting stent (DES) in the main vessel and DEB in the side branch, compared to stepwise provisional two-stent strategy in patients with true bifurcation lesions. A total of 500 patients with de novo true coronary bifurcation lesions, treated with a stepwise provisional approach and an unsatisfactory result of the side branch after main vessel stenting (≥ 70% stenosis and/or < thrombolysis in myocardial infarction III flow), will be randomized in a 1:1 ratio to receive either treatment with a DEB or with a DES in the side branch. The primary endpoint is a composite endpoint of the occurrence of all-cause death, periprocedural or spontaneous myocardial infarction and/or target vessel revascularization at the anticipated median 2-year follow-up. The Hybrid DEB study will compare in a multicenter, randomized fashion a hybrid DEB approach with a stepwise provisional two-stent strategy in patients with true bifurcation lesions. ClinicalTrials.gov no. NCT05731687.